Unlike Many Disease Resistances, Rx1-Mediated Immunity to Potato Virus X Is Not Compromised at Elevated Temperatures - Richard, Manon M. S.; Knip, Marijn; Aalders, Thomas; Beijaert, Machiel S.; Takken, Frank L. W. (Frontiers in Genetics, 2020)
Specificity in the plant immune system is mediated by Resistance (R) proteins. Most R genes encode intracellular NLR-type immune receptors and these pathogen sensors require helper NLRs to activate immune signaling upon pathogen perception. Resistance conferred by many R genes is temperature sensitive and compromised above 28 C. Many Solanaceae R genes, including the potato NLR Rx1 conferring resistance to Potato Virus X (PVX), have been reported to be temperature labile. Rx1 activity, like many Solanaceae NLRs, depends on helper-NLRs called NRC’s. In this study, we investigated Rx1 resistance at elevated temperatures in potato and in Nicotiana benthamiana plants stably expressing Rx1 upon rub-inoculation with GFP-expressing PVX particles. In parallel, we used susceptible plants as a control to assess infectiousness of PVX at a range of different temperatures. Surprisingly, we found that Rx1 confers virus resistance in N. benthamiana up to 32 °C, a temperature at which the PVX::GFP lost infectiousness. Furthermore, at 34 °C, an Rx1-mediated hypersensitive response could still be triggered in N. benthamiana upon PVX Coat-Protein overexpression. As the Rx1-immune signaling pathway is not temperature compromised, this implies that at least one N. benthamiana helper NRC and its downstream signaling components are temperature tolerant. This finding suggests that the temperature sensitivity for Solanaceous resistances is likely attributable to the sensor NLR and not to its downstream signaling components.